2023
DOI: 10.3928/1081597x-20231101-01
|View full text |Cite
|
Sign up to set email alerts
|

Angle Kappa Influence on Multifocal IOL Outcomes

Avi Wallerstein,
Chelsea Ridgway,
Damien Gatinel
et al.

Abstract: Purpose: To characterize angle kappa and study the relationship between preoperative angle kappa and postoperative refractive accuracy, visual outcomes, and patient satisfaction in a large population of eyes with multifocal intraocular lens (MIOL) implantation. Methods: A comprehensive electronic medical record chart review of 26,470 consecutive eyes that underwent immediate sequential bilateral cataract or refractive lens exchange with MIOLs was conduc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 30 publications
2
2
0
Order By: Relevance
“…We demonstrated that preoperative angle kappa did not have a predictive clinical impact on postoperative MIOL visual outcomes, refractive accuracy, subjective patient satisfaction at near, intermediate and far distance, nor with the likelihood of recommending an MIOL procedure to friends and relatives. 2 Our study also noted a larger angle kappa in right vs. left eyes. Liu et al add validity to our existing findings 2 and confirms, along with several previous studies, 3–9 that angle kappa as a single variable cannot be used to determine MIOL candidacy.…”
Section: Dear Editorsupporting
confidence: 69%
See 3 more Smart Citations
“…We demonstrated that preoperative angle kappa did not have a predictive clinical impact on postoperative MIOL visual outcomes, refractive accuracy, subjective patient satisfaction at near, intermediate and far distance, nor with the likelihood of recommending an MIOL procedure to friends and relatives. 2 Our study also noted a larger angle kappa in right vs. left eyes. Liu et al add validity to our existing findings 2 and confirms, along with several previous studies, 3–9 that angle kappa as a single variable cannot be used to determine MIOL candidacy.…”
Section: Dear Editorsupporting
confidence: 69%
“… 2 Our study also noted a larger angle kappa in right vs. left eyes. Liu et al add validity to our existing findings 2 and confirms, along with several previous studies, 3–9 that angle kappa as a single variable cannot be used to determine MIOL candidacy. The novelty of the study by Liu et al lies in reaching the same conclusion with angle kappa measurements taken by Pentacam and adding photic phenomena data.…”
Section: Dear Editorsupporting
confidence: 69%
See 2 more Smart Citations